Need analysis for the development of chemical literation integrated problem-solving module - Rodi Edi; Maefa Eka Haryani; Eka Ad’hiya (Pascasarjana Universitas Negeri Medan, 2021)
This research is a descriptive survey research to analyze student needs for chemical literation integrated problem solving modules. The questionnaire was given to 89 active students of chemistry education at Sriwijaya University who were selected using a non-probability sampling technique. The results of the questionnaire were then analyzed using descriptive statistical tests. The results of this study indicate that students understand the qualifications needed as an undergraduate and are in the process of achieving this, and they agree to develop problem-solving integrated chemical literacy based basic chemistry modules as teaching materials that can help them to achieve the competences.Keywords: Chemical literation, Problem-Solving, Module, Chemistry